Statutory wills: Doing the right thing under the Mental Capacity Act 2005. (January 2017) - Milward, Kathryn; Curtice, Martin; Harding, Rosie
Summary: Statutory wills are made under the Mental Capacity Act 2005 (MCA) for persons who lack testamentary capacity. Mental health practitioners are likely to be familiar with many of the provisions of the MCA and the test for testamentary capacity. However, they may not have encountered statutory wills. This article explains the procedure for applying for a statutory will, including the role of medical practitioners. Salient legal cases are summarised to highlight the difficulties in applying a best interests framework for decision-making in the context of statutory wills. Finally, this article considers how the United Nations Convention on the Rights of Persons with Disabilities (CRPD) might affect not only on statutory wills, but also the wider provisions of the MCA. Learning Objectives: Be able to explain statutory wills and the application procedure to a patient or carer Understand the differences between the test for testamentary capacity (as established in Banks v Goodfellow (1870)) and assessing capacity under the MCA Appreciate how the CRPD might affect the decision-making process, not only for statutory wills but for all decisions made under the MCA